Imprinted Zeolite Modified Carbon Paste Electrode as a Selective Sensor for Blood Glucose Analysis by Potentiometry - Miratul Khasanah; Alfa Akustia Widati; Usreg Sri Handajani; Muji Harsini; Bahrotul Ilmiah; Irene Dinda Oktavia (Universitas Gadjah Mada, 2020)
Imprinted zeolite modified carbon paste (carbon paste-IZ) electrode had been developed as a sensor to analyze blood glucose content by potentiometry. The used zeolite was Lynde Type A (LTA) that synthesized with a mole ratio of Na2O, Al2O3, SiO2 and H2O of 4:1:1.8:270, respectively while non-imprinted zeolite was prepared with a mole ratio of glucose/Si of 0.0306. Glucose was then extracted from the zeolite framework using hot water (80 °C) to produce imprinted zeolite (IZ). The carbon paste-IZ electrode prepared from activated carbon, paraffin pastilles, and IZ with a mass ratio of 5:4:1 showed the best performance. The modified electrode demonstrated the measurement range of 10–4-10–2 M, the Nernst factor of 29.55 mV/decade, the response time less than 120 s, and the detection limit of 5.62 × 10–5 M. Ascorbic acid, uric acid, urea and creatinine did not interfere on the glucose analysis by potentiometry. Comparison test with spectrophotometry showed an accuracy of (90.7 ± 1.4)% (n = 5), while the application of the electrode to analyze five spiked serum samples showed recovery of (92.2 ± 1.3)% (n = 5). The electrode was stable for up to 9 weeks (168 times usage). Based on its performance, the developed electrode can be applied to analyze glucose in human serum sample and recommended for used in the medical field.